Resource utilization and admission trends in medical wards in a district hospital in South Africa - Mautjana, Maria Ntana (My University, 2011)
Introduction: South Africa is currently facing a quadruple burden of diseases: poverty related conditions, emerging chronic diseases, injuries and HIV/AIDS. Increasing burden of these diseases is having a detrimental impact on service delivery particularly in rural areas, where the majority of the population are dependent on public health system. Although numerous epidemiological studies had been done in the past to determine the prevalence of these conditions, only a few studies have attempted to quantify the effect of these diseases on health facilities such as admission rate, bed occupancy rate and resource utilisation. More data is required to develop a better understanding of their impact and to guide development of appropriate response strategies. Aim of the study: To `analyse trends of admissions and resource utilisation in adult medical wards of a rural district hospital in South Africa. Methodology: This was a descriptive cross-sectional, retrospective study involving an analysis of data from adult medical wards in the George Masebe Hospital (a district hospital in Limpopo Province) for six months in 2009. Results: The study found average number of admissions per month was 148, their length of stay varied from one day to more than a year. Their median age was 44 years. They were black, had no medical aid and unemployed and the majority of them were dependent on social welfare grant. The most common health problems diagnosed amongst the medical admissions were HIV related conditions such as gastro-enteritis, pneumonia, AIDS and tuberculosis as well as other chronic diseases such as diabetes mellitus. A striking discovery was the high incidence of mental illness amongst the admissions. The majority of them were discharged home. The crude death rate was 190 per 1000 admissions and the main cause of death was HIV related conditions. The average direct expenditure per month was R 1,040,579. The expenditure for salaries was the main expenditure (54%) followed by Allied health services (29%). The average expenditure per patient was R 7,039 (R 7,548 for female patients and R 6454 for male patients). v Conclusion: This was the first study on admission trends resource utilisation in this Hospital and in the Limpopo Province. The evidence from this study would hopefully steer the re-organisation of some of the Hospital services, more especially the establishment of a step-down ward facility within the Hospital. This study has recognised that the increased number of admissions in rural district hospitals often result from double burden of infectious and chronic diseases. More studies on the subject are needed to identify their impact on resource utilisation at these hospitals.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Public Health in the field of Hospital Management Johannesburg, 2011
Keywords: Utilization Review; Hospital Administration